3x(2y + 1)
3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)
y^(3) - 2y^(2) + 4y Factor out 'y' Hence y(y^2 - 2y + 4) This will not factor any further.
2y(2y - 1)(2y - 3)
2y(2y - 1)(2y - 3)
3x(2y + 1)
The GCF is 3xy.
3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)
(3x - 2y)(9x^2 + 6xy + 4y^2)
3y(3x - 2y)(9x^2 + 6xy + 4y^2)
y^(3) - 2y^(2) + 4y Factor out 'y' Hence y(y^2 - 2y + 4) This will not factor any further.
xy(7+2y-3x)-6xy
6xy
2y(2y - 1)(2y - 3)
2y(2y - 1)(2y - 3)
16
2y + 2xy' + 4y + 4xy' = 0 6y + 6xy' = 0 y' = -y/x